(untitled) (World Science, 2018)
The Armenian insurance market has undergone major changes in the transition to a market economy. Growth tendencies were observed in almost all insurance indicators. At present, the RA Central Bank is the body overseeing the financial system of RA. The positive shifts in the insurance market are partially conditioned by its activities. The article presents the main directions of the activities of insurance companies in RA. Insurance premiums and insurance indemnities have undergone comparative analysis. In a number of countries the insurance is one of the most important prerequisites for the provision of agricultural loans through which banks try to mitigate their credit risk. Agricultural insurance is not implemented in the Republic of Armenia, which negatively affects the stability and development of the sector. Taking into account the advantages of compulsory insurance and the current socio-economic conditions created in Armenia, the article recommends to implement compulsory insurance of agricultural credits. The necessity of introduction of credit insurance in the RA agrarian sphere has been justified, the reasons of non-implementation of agricultural credit insurance has been raised, and the main results expected when implementing agricultural credit insurance has been presented.